Environmental impacts of ecotourism on mangrove : case study of Kuala Selangor Nature Park - Ali, Maisarah; Musa, Mohd Faiz (Marginal Areas Research Group, 2011)
Mangrove is one of the natural settings, which fall under wetland forest category with diverse ecosystem. With its location between the upland and coastal ecosystem, mangrove forest is an ecotone zone; a region of transition between two biological communities with diversity of wildlife habitat and human natural resources. The valuable intrinsic (natural) ecological functions and socio-economic values of mangrove forest make it one of the reasons why mangrove forest has been exploited under the name of development for example aquaculture production, timber or chip wood production and also tourism development.